Pemanfaatan Radio Frequency Identification (RFID) Berbasis Internet of Things (IoT) untuk Perancangan Palang Pintu Otomatis di Universitas Nurul Jadid - Arie Wahyudi; Fathorazi Nur Fajri; Syaiful Syaiful (Universitas Nurul Jadid, 2020)
Today's technology is still developing and creating new innovations and works. One of them is Radio Frequency Identification (RFID) technology. Automatic doorstop using web-based RFID is a tool that makes it easier for doorman guards because this way they don't have to open the latch manually. This system uses a data input process that utilizes RFID to speed up time in the data input process. This system uses the PHP and MYSQL programming language as the database and uses PHP in making this website. With the web-based system, RFID matches the data in the database and the door will open automatically if the data matches the data in the database.